Distance learning during the COVID-19 pandemic: the experience of students in a large hungarian university - Prescott-Pickup Francis J. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The global COVID-19 pandemic was first identified in Europe in France, when the first case was confirmed on 24 January 2020 (WHO, 25 January 2020). The first major outbreak occurred in Italy in the following weeks and the virus rapidly took hold in other countries in western Europe. On 13 March the World Health Organisation declared that Europe had become the epicentre of the pandemic (NEBEHAY, 13 March 2020). Italy became the first country in Europe to implement a national lockdown on 9 March and similar lockdowns quickly followed all over Europe. By 18 March more than 250 million people were living in some form of lockdown (HENLEY & OLTERMANN, 18 March 2020). The effect of national lockdowns on all aspects of life was profound but perhaps nowhere was it more difficult for people to deal with than in the education sector, where teachers, students and parents were suddenly forced to deal with a situation they had been given almost no time to prepare for – enforced distance learning. This entailed the necessity for schools and institutes of higher education to rapidly organise online learning for students, either synchronously or asynchronously, using a variety of online applications. As Harrison (2020) puts it: Since many countries have imposed a lockdown on movement, and many schools have subsequently closed their doors, vast numbers of previously tech-shy teachers are having to learn very quickly how to teach using online resources. This might be through delivering lessons using virtual classrooms or providing online self-study material for students, both of which may be new modes of lesson delivery for many. (par. 1)
Távoktatás a COVID–19-világjárvány idején: hallgatók tapasztalata egy nagy magyar egyetemen
Keywords: distance learning; Covid–19 pandemic; tertiary education; 21st century learning; qualitative research